PROPOSED GAMIFICATION CONCEPT TO INCREASE DONOR ENGAGEMENT FOR GREEN FUND DIGITAL PHILANTHROPY PLATFORM CASE STUDY: GREENERATION FOUNDATION - Perdana Kusuma, Fikli
Humans and the environment are two natural elements that can never be separated. The environment provides all human needs for survival and humans have also used the environment from 2.5 million years ago to this moment. Currently, the environmental damage that is accelerating cannot be separated from human intervention itself, and the solution should also start from human hands as well. The government as the stakeholder has the biggest responsibility because the policies taken tend to exploit natural resources without being balanced with solutions for the restoration process. This is illustrated by data from the Ministry of Finance of the Republic of Indonesia, in an initiative to address environmental issues and climate change, the Indonesian government has prepared a climate change budget. From 2018 to 2020, the total budget owned is 307.84 trillion rupiah. This amount only covers 4.3% of the Anggaran Pendapatan dan Belanja Negara (APBN). This budget is only able to meet 34% of the budget needed for climate change. One of the solutions that the government can do is to provide a space for cross-stakeholder collaboration such as the community, non-profit organizations, youth communities in Indonesia with the same enthusiasm to present solutions for environmental restoration, it is hoped that this can accelerate solutions to environmental damage. From this problem, Greeneration Foundation is trying to be present to offer a concrete solution by inviting the public to donate a minimum of Rp. 10,000 for a sustainable environmental solution by adapting technological developments that are implemented on an online Green Fund Digital Philanthropy donation platform. As a new institution that operates as a fundraiser, Greeneration Foundation has quite a tough challenge to be able to improve aspects of donor involvement so that they can continue to donate to Green Fund Digital Philanthropy platform. One way that can be done to increase donor involvement is to implement a gamification scheme on the donation platform, but in its implementation it requires a big commitment from Greeneration Foundation and must pay attention to the needs of donors. To answer these problems, an interview process was conducted with internal stakeholders to determine the capacity and capability of the organization in implementing the gamification scheme combined with an external survey to obtain feedback from the public regarding the need to implement a gamification scheme on a donation platform. The results of interviews with internal stakeholders of Greeneration Foundation found that in terms of the big strategy the organization really supports the gamification implementation process, this illustrates that Greeneration Foundation has the desire to make a donation platform that is fun and not boring by presenting new experiences to donors so that they continue to channel their donations through the platform Green Fund Digital Philanthropy donations, but in the process they still encounter many obstacles such as lack of funding, human resources, and platform strategies. This is in line with the results of the analysis obtained from the external survey process, the result is that as many as 86% of the 100 respondents think gamification can increase donor involvement to donate by implementing gamification components such as donation trips and donation missions, this is a concern for donors because they need experience that to increase motivation in making donations. This should be of more concern to Greeneration Foundation that implementing a gamification scheme can increase the involvement of donors to continue donating to Green Fund Digital Philanthropy platform. The analysis results obtained were followed up by making a solution proposal that could be used as a reference by Greeneration Foundation to accelerate the process of implementing a gamification scheme on Green Fund Digital Philanthropy platform in 2023.